Aqueous magnesium as an environmental selection pressure in the evolution of phospholipid membranes on early earth. (15th February 2018) - Dalai, Punam; Ustriyana, Putu; Sahai, Nita
Abstract: Early compartmentalization of simple biomolecules by membrane bilayers was, presumably, a critical step in the emergence of the first cell-like entities, protocells. Their membranes were likely composed of single chain amphiphiles (SCAs), but pure SCA membranes especially those with short-chains are highly unstable towards divalent cations, which are ubiquitous in aqueous environments. The prebiotic synthesis of phospholipids (PLs), even in only trace amounts, may also have been possible. PL membranes are much more stable towards divalent cations. Here, we show the transition of fatty acid membranes to mixed fatty acid-PL and, finally, to PL membranes in the presence of Mg 2+, which acts as an environmental selection pressure, and we propose different mechanisms for the observed increased Mg 2+ -immunity. The "fatal" concentration ([Mg 2+ ]fatal ) at which vesicles are disrupted increased dramatically by an order of magnitude from OA to mixed to POPC vesicles. Two mechanisms for the increasing immunity were determined. The negative charge density of the vesicles decreased with increasing POPC content, so more Mg 2+ was required for disruption. More interestingly, Mg 2+ preferentially bound to and abstracted OA from mixed lipid membranes, resulting in relatively POPC-enriched vesicles compared to the initial ratio. The effect was the most dramatic for the largest initial OA-POPC ratio representing the most primitive protocells. Thus, Mg 2+ acted to evolve the mixed membrane composition towards PL enrichment. To the best of our knowledge, this is the first report of selective lipid abstraction from mixed SCA-PL vesicles. These results may hold implications for accommodating prebiotic Mg 2+ -promoted processes such as non-enzymatic RNA polymerization on early Earth.